Impact of nocturia on patients' health‐related quality of life and healthcare resource utilisation compared with OAB and BPH: Results from an observational survey in European and American patients. Issue 12 (10th September 2019) - Zeng, Veronica Y.; Milligan, Gary; Piercy, James; Anderson, Peter; Andersson, Fredrik L.
Abstract: Objective: To evaluate the impact of nocturia on patients' quality of life and healthcare resource utilisation (HRU) compared with overactive bladder (OAB) and benign prostatic hyperplasia (BPH). Methods: Data were drawn from a multinational (France, Germany, Spain, UK and US) survey of physician and patient‐reported outcomes. The patient groups of interests were those diagnosed with only nocturia, with only OAB, and with only BPH. Health‐related quality of life (HRQoL) and productivity measures were derived from the EuroQoL‐5D, OAB‐q and the Work Productivity and Activity Impairment Questionnaire (WPAI). Measures of HRU included lower urinary tract symptoms (LUTS)‐relevant surgeries, hospitalisations, current use of pads and related physician visits. Bivariate and multivariate regression analyses were used to evaluate associations between HRQoL/HRU/Productivity and nocturia status. Multivariate analysis was used to address any potential confounding factors among the groups, ie age, gender, body mass index (BMI), ethnicity and comorbidities. Results: A total of 3552 patients were identified including 358 nocturia patients, 1415 OAB patients and 1779 BPH patients. The mean age of the nocturia patients was 61.2 years with a mean BMI of 27.3. About 60.6% were women, 87.2% were Caucasian, and their most common comorbidities included depression, hypertension and diabetes. In terms of impact, nocturia patients were significantly worse off than OAB patients in their HRQoL. There was no significant difference regarding HRU and productivity measurement. Nocturia patients also presented with significantly worse HRQoL and lower productivity compared with BPH patients. Nocturia patients also had more physician visits. Conclusions: Nocturia should be emphasised as a standalone LUTS disease with substantial patient impact. Compared with OAB and/or BPH, nocturia patients presented with a significant reduction on patients' quality of life, reduced work productivity and increased utilisation of healthcare resources.